Towards 5th Generation Cellular Mobile Networks - Cheng, Peng; Weily, Andrew R. Weily; Guo, Y. Jay (Journal of Telecommunications and the Digital Economy, 2014)
Cellular mobile networks have enabled ubiquitous communications and largely changed the way we live and work. At the same time, the network itself has been undergoing significant changes in the process of meeting our ever increasing demands on data rate and quality of service. In this article, we show the path of the evolution in both standards and techniques and provide our vision for the future of the cellular networks. We review the evolution of international standards for cellular mobile networks in the last two decades, describe how the network layout has been migrating from rigid cellular architecture to random and dense small cells, and provide an in-depth discussion on potential enabling techniques for the next generation (5G) cellular networks, particularly massive MIMO and multiband base-station antennas.